2019
DOI: 10.3390/ani9050277
|View full text |Cite|
|
Sign up to set email alerts
|

Phenotypic Stability of Sex and Expression of Sex Identification Markers in the Adult Yesso Scallop Mizuhopecten yessoensis throughout the Reproductive Cycle

Abstract: The objective of the present study was to analyze the phenotypic stability of sex after sex differentiation in the Yesso scallop, which is a gonochoristic species that has been described as protandrous. So far, no study has investigated in detail the sexual fate of the scallop after completion of sex differentiation, although bivalve species often show annual sex change. In the present study, we performed a tracking experiment to analyze the phenotypic stability of sex in scallops between one and two years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
(72 reference statements)
1
7
0
Order By: Relevance
“…In the present study, we identified single copy FoxL2 and Dmrt1L in A. irradians . As expected, FoxL2 and Dmrt1L showed female- and male-biased expression in the gonad, respectively, similar to the expression patterns of FoxL2 and Dmrt in other bivalves, such as the gonochoristic scallop P. yessoensis ( Li et al, 2018 ; Nagasawa et al, 2019 ), the sequential hermaphrodites C. gigas ( Zhang et al, 2014 ) and P. margaritifera ( Teaniniuraitemoana et al, 2014 , 2015 ). Spatial expression of FoxL2 and Dmrt1L in the ovary and testis revealed that both genes were distributed in follicle cells and germ cells within the follicle, consistent with previous research in the gonochoristic scallop C. farreri ( Liu et al, 2012 ) and P. yessoensis ( Li et al, 2018 ), and the sequential hermaphrodite C. gigas ( Naimi et al, 2009 ).…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, we identified single copy FoxL2 and Dmrt1L in A. irradians . As expected, FoxL2 and Dmrt1L showed female- and male-biased expression in the gonad, respectively, similar to the expression patterns of FoxL2 and Dmrt in other bivalves, such as the gonochoristic scallop P. yessoensis ( Li et al, 2018 ; Nagasawa et al, 2019 ), the sequential hermaphrodites C. gigas ( Zhang et al, 2014 ) and P. margaritifera ( Teaniniuraitemoana et al, 2014 , 2015 ). Spatial expression of FoxL2 and Dmrt1L in the ovary and testis revealed that both genes were distributed in follicle cells and germ cells within the follicle, consistent with previous research in the gonochoristic scallop C. farreri ( Liu et al, 2012 ) and P. yessoensis ( Li et al, 2018 ), and the sequential hermaphrodite C. gigas ( Naimi et al, 2009 ).…”
Section: Discussionsupporting
confidence: 80%
“…In T. squamosa, sex is more likely to be dominated by the interaction of multiple genes. Next-generation sequencing technology has been utilized to study the genes related to reproduction in various species [18][19][20][21][22][23][24], but no data is currently available on the gonad transcriptome of T. squamosa.…”
Section: Introductionmentioning
confidence: 99%
“…The Dmrt1 gene (DN11344_c0_g1_i5), usually involved in testis development, was also found up-regulated in P. lividus testis. As in many other species, including sea urchins, Dmrt1 is described as playing a major role in sex determination and differentiation in several vertebrate and invertebrate species (Zhang and Zarkower 2017, Nagasawa et al 2019, Sun et al 2019). In accordance with the report of (Sun et al 2019) in M. nudus species, also the Nanos (DN9673_c0_g1_i2) gene in P. lividus is up-regulated in female gonads.…”
Section: Resultsmentioning
confidence: 95%